Factors Associated With Sexual Coercion in a Representative Sample of Men in Australian Prisons - Simpson, P.; Reekie, J.; Butler, Tony; Richters, J.; Yap, L.; Grant, L.; Richards, A.; Donovan, B. (2015)
Very little research has focused on men or prisoners as victims of sexual violence. This study provides the first population-based analysis of factors associated with sexual coercion of men in Australian prisons, and the first to use a computer-assisted telephone interview to collect this information in a prison setting. A random sample of men in New South Wales and Queensland prisons were surveyed using computer-assisted telephone interviewing. We asked participants about sexual coercion, defined as being forced or frightened into doing something sexually that was unwanted while in prison. Associations between sexual coercion in prison and sociodemographics, sexual coercion history outside of prison, and prison-related factors were examined. Logistic regression was used to estimate adjusted odds ratios in examining factors associated with sexual coercion in prisons. Of 2626 eligible men, 2000 participated. Participants identifying as non-heterosexual and those with a history of sexual coercion outside prison were found to be most at risk. Those in prison for the first time and those who had spent more than 5 years in prison ever were also more likely to report sexual coercion. Although prison policies and improving prison officer training may help address immediate safety and health concerns of those at risk, given the sensitivity of the issue and likely under-reporting to correctional staff, community-based organizations and prisoner peer-based groups arguably have a role too in providing both preventive and trauma-focused support.